Efficacy and Safety of Avatrombopag in Patients With Thrombocytopenia: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Li, Chunlu; Li, Xiaoxuan; Huang, Feihong; Yang, Jing; Wu, Anguo; Wang, Long; Qin, Dalian; Zou, Wenjun; Wu, Jianming (Frontiers in Pharmacology, 2019)
Background: Avatrombopag is a novel oral, nonpeptide thrombopoietin receptor agonist (TPO-RA). A few studies have shown that avatrombopag is effective against thrombocytopenia. However, no systematic review has been conducted on the efficacy and safety of avatrombopag. Therefore, the aim of this study was to comprehensively assess the efficacy and safety of avatrombopag patients with thrombocytopenia. Methods: Databases including Medline, PubMed, Embase, the Cochrane Library and ClinicalTrials.gov were searched for randomized controlled trials that compared avatrombopag with placebo in patients with thrombocytopenia. The deadline was March 2019. Results: In total, 743 patients were analyzed in five clinical trials. Patients treated with avatrombopag achieved higher platelet response (OR: 17.71, 95% CI [11.01 to 28.48], p < 0.00001) than with placebo. Avatrombopag produced an absolute increment in platelet count (WMD: 31.13%, 95% CI [22.27 to 39.99], p < 0.00001) unlike the placebo. In addition, the incidence of serious adverse events (RR: 1.18, 95% CI [0.72 to 1.93], p = 0.51) and deaths (RR: 0.93, 95% CI [0.19 to 4.45], p = 0.93) in patients treated with avatrombopag were not significantly different from that in patients treated with placebo. The incidence of adverse events in patients treated with avatrombopag was slightly higher than that in patients treated with placebo (RR: 1.25, 95% CI [1.05 to 1.49], p = 0. 01) after one trial with high heterogeneity was removed. Conclusions: This meta-analysis showed that avatrombopag was an effective treatment for thrombocytopenia, but there is sufficient evidences to indicate that adverse events may occur.